2007
DOI: 10.1002/cncr.23072
|View full text |Cite
|
Sign up to set email alerts
|

A phase II evaluation of goserelin and bicalutamide in patients with ovarian cancer in second or higher complete clinical disease remission

Abstract: The mechanism of the gas‐phase elimination kinetics of 2‐ethoxypyridine has been studied through the electronic structure calculations using density functional methods: B3LYP/6‐31G(d,p), B3LYP/6‐31++G(d,p), B3PW91/6‐31G(d,p), B3PW91/6‐31++G(d,p), MPW1PW91/6‐31G(d,p), MPW1PW91/6‐31++G(d,p), PBEPBE/6‐31G(d,p), PBEPBE/6‐31++G(d,p), PBE1PBE1/6‐31G(d,p), and PBE1PBE1/6‐31++G(d,p). The elimination reaction of 2‐ethoxypyridine occurs through a six‐centered transition state geometry involving the pyridine nitrogen, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Monotherapy studies using tamoxifen, aromatase inhibitors, and GnRH analogues had yielded variable results with objective response rates ranging between 0 and 56%. 17,[19][20][21][34][35][36][37][38] Combinatorial treatment regimens combining tamoxifen and goserelin or tamoxifen and Gefitinib had obtained results with objective response rates of up to 11.5%. 39,40 Few of these studies had selected patients based on the immunohistochemically determined estrogen receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…Monotherapy studies using tamoxifen, aromatase inhibitors, and GnRH analogues had yielded variable results with objective response rates ranging between 0 and 56%. 17,[19][20][21][34][35][36][37][38] Combinatorial treatment regimens combining tamoxifen and goserelin or tamoxifen and Gefitinib had obtained results with objective response rates of up to 11.5%. 39,40 Few of these studies had selected patients based on the immunohistochemically determined estrogen receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…Other hormonal agents that have been evaluated in this context are progesterone receptor agonists (Ho 2003, Niwa et al 2008, Diep et al 2013 and antiandrogens, including flutamide and bicalutamide (Levine et al 2007).…”
Section: Endocrine Treatment Approachesmentioning
confidence: 99%
“…In women with epithelial ovarian cancer, researchers have reported an association between short poly-glutamine tracts in the AR and decreased progressionfree and overall survival [58]. These associations ultimately led to the evaluation of anti-androgen therapy in two clinical trials, neither of which demonstrated significant improvement in progression-free or overall survival [59,60]. Unfortunately, these trials were performed in heavily treated women with refractory disease leaving the efficacy of an anti-androgen as first-line therapy an open question.…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%